PENGARUH BIOCHAR SEKAM PADI TERHADAP SIFAT FISIK TANAH DAN HASIL TANAMAN JAGUNG (Zea mays) DI KELURAHAN LAPE KECAMATAN AESESA - Yosefina Fifi Janu; Charly Mutiara (AGRICA, 2021)
This study aims to determine the condition of the physical properties of the soil and maize yields given rice husk biochar in Lape Village, Aesesa District. The continuous use of inorganic fertilizers will have a negative impact on the soil such as destroying the physical properties of the soil and reducing maize yields. Therefore, this research is a descriptive study. Determination of soil samples using purposive sampling method with the criteria of land cultivation of corn and rice husk biochar. The variables observed were soil color, structure, texture, porosity, bulk density, moisture content, temperature, humidity and maize yield. The results showed that the criteria for the physical properties of the soil in the maize cultivation area were dusty clay soil texture and categorized as S1 class, soil color was dominated by 10 YR 2/1 Black and categorized as S1 class, and soil structure was dominated by granular criteria. B0 content density value: 1.01; B2: 0.9; B3: 0.87; B4: 0.81; B4: 0.8 and categorized as S2 class, soil porosity value B0: 61.76; B1: 65.91; B2:67,18; B3: 69.41; B4; 69.89 and categorized as S1 class. Value of water content B0: 36.78; B1:41,14; B2: 40.82; B3: 35.06; B4: 39.55 and categorized into class N. temperature analysis results B0: 33.75; B1: 34.00; B2: 32.75; B3: 33.25; B4: 34.00 and can be categorized as class N. Moisture analysis results B0: 67.00; B1: 68.00; B2: 64.50; B3: 66.25; 68.00 and categorized in S1 class. And maize yields. Corn kernels yield tan-1(g) B0: 347.30; B1: 360.40; B2: 380.70; B3: 385.40; B4: 401.35. Yield of shelled corn ha-1(tons) B0: 9.26; B1: 9.61; B2: 10,15; B3: 10.28; B4: 10.70